(untitled) (Research, Society and Development, 2021)
This paper aims to verify the quality of factor structure, invariance and differences of the turnover intention scale in workers. The theme regarding turnover in the workplace has been studied frequently in recent years, which is a concern for workers and managers, because it directly affects the quality and efficiency of organizations, capable of compromising the strategies of competitiveness, productivity and innovation. The study had the participation of 219 workers, aged over 18 years old, distributed in the cities of Natal-RN and João Pessoa-PB, in the public and private sectors, men and women. They answered, besides the sociodemographic data, the Turnover Intention Scale, the Survey of Perceived Organizational Support, and the Scale of Perception of Bullying in the World of Work. Descriptive statistics, Pearson correlations, Student’s t-test, Anova, and confirmatory factorial analysis were performed. From the findings of this study, the scale is reliable, consistent, and invariable, especially when comparing the RN and PB samples. The psychometric indicators both corresponded to what was expected and were technically within the required statistical criteria. Thus, it is considered that this measure is intended for use in the organizational context, being important for the evaluation of human resources in organizations, focusing both on diagnosis and labor prognosis.